Variability of the thousand-seed weight in bread wheat (Triticum aestivum L.) - Urošević Dušan; Knežević Desimir; Matković-Stojšin Mirela; Živić Jelica; Mićanović Danica; Kondić Danijela; Zečević Veselinka (Agroznanje)
The thousand-seed weight (TSW) is one of the traits which is related to yield and milling quality of wheat. The aim of this work was to study the variability of the thousand-seed weight of bread wheat varieties grown under different environmental conditions. Fifty wheat varieties in a field experiment designed as a randomized block system were used for this study in three replications on the field in Kraljevo, Serbia during two vegetation seasons (2015-2017). The seeds were sown at 0.10 m distance in 1.0 m long rows spaced apart 0.2 m. Sixty plants at the full maturity stage (20 plants replication-1) were harvested and used for analyzing the thousand-seed weight. The analysis of variance was performed by MSTAT C (5.0 version). Similarities among wheat varieties were analyzed by using the hierarchical method of the Euclidean distance. The results have shown significant differences in the thousand-seed weight among varieties in both years. On average, in the first vegetation season the lowest thousand-seed weight (39.14 g) was recorded in the Lepenica variety, while the highest thousand-seed weight (54.66 g) was recorded in the Zadruga variety. In the second vegetation season, the thousand-seed weight varied from the lowest in NS Rana 2 (34.57 g) to the highest in Šumadinka (50.33 g). The similarity was illustrated on a dendogram containing four clusters in the first year and six clusters of varieties in the second year. The prominent cluster contained different numbers and compositions of varieties with the highest degree of similarity. The differences in average of the thousand-seed weight were determined by the genetic, environmental factor and by genotype/environment interaction.